تاريخ إمارات الساحل المتصالح في كتب الرحالة الأجانب رحلة ويليام . ج . بلجريف أنموذجاً - الهامور, سعاد; المغنى, عبدالله (جامعة الوادي - University of Eloued, 2022)
منذ مطلع القرن التاسع عشر الميلادي ومنطقة الخليج ( والتي من بينها منطقة الإمارات ) كانت قبلة للرحالة على اختلاف جنسياتهم ودياناتهم وتوجهاتهم السياسية وأهدافهم، فقاموا بتدوين مشاهداتهم وانطباعاتهم، ومن بينهم الرحالة ويليام . ج . بلجريف والذي كانت رحلته بالغة الأهمية، حيث قام بتدوين مشاهدات وانطباعات متنوعة ومختلفة الجوانب كالاقتصادي والاجتماعي وغيرها، فضلاً عن هذا أن رحلته أصبحت مصدراً للدراسات التاريخية. وخلصت الدراسة أنه لا ننكر بأن كتابات بلجريف كانت أحد المصادر التي تناولت تاريخ الإمارات خلال تلك الحقبة التي لم يكن فيها للتدوين أي اهتمام من أبناء المنطقة، إضافة إلى أن رحلته كانت ولازالت رافداً لا غنى عنه في الكتابة التاريخية للمنطقة. Since the beginning of the nineteenth century AD, the Gulf region, which includes the Emirates region, has been a destination for travelers of different nationalities, religions, political orientations, and goals, whose their concern was on recording their observations and impressions about the region. Among them was the traveler, William. C Belgrave, whose journey had a great importance, as he recorded various observations and impressions in various aspects such as economic, social fields and others. In addition to this, his trip became a great resource for historical studies. The study concluded that we do not deny that Belgrave's writings were one of the sources that dealt with the history of the Emirates during that era in which documentation did not have any interest from the people of the region. In addition to that his journey was and still is an indispensable tributary of the historical writing of the region..
مقال
Keywords: الإمارات ; الرحالة الغربيين ; يليام بلجريف; Emirates ; Western travelers ; William Palgrave